GAMBARAN SISTEM PENGELOLAAN LIMBAH PADAT DOMESTIK DI RUMAH SAKIT ISLAM A.YANI SURABAYA - Dita Amelia Sari; Abdul Hakim Zakkiy Fasya; Akas Yekti Pulih Asih; Novera Herdiani (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2023)
Hospital waste can threaten surfaces, water, air, soil, environment and human health. Almost 80% of the waste produced by hospitals is in the form of non-medical waste, and 20% is in the form of medical waste. Based on the total amount of waste generated by health service activities, about 85% is general non-hazardous waste which is comparable to domestic waste. The purpose of this study is to describe the domestic solid waste management system at Isam A. Yani Hospital, Surabaya.This type of research is a quantitative study with a cross-sectional approach. pene The population in this study is to 5 informants. This research uses purposive sampling method. The data used in this study are primary and secondary data.The results of the research at the stage of handling domestic solid waste for storage have distinguished between organic and non-organic waste, the transporter uses PPE and is stored in the TPS for 1 day. The facilities available are trolleys with uk 660 liters and 240 liters, sinks, green carts, dustbins, cikrak etc. Vector control is always carried out when there is a density of vector animals. Conclusion The conclusion of the domestic solid waste management system at the Islamic Hospital A. Yani Surabaya is that RSI has carried out the stages of waste management in accordance with existing regulations.Keywords: Hospitals, Domestic waste, Waste management